Indigenous and decolonizing studies in education mapping the long view - Smith, Linda Tuhiwai 1950-; Tuck, Eve; Yang, K. Wayne (New York, NY Routledge, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.--Publisher's description.
Literacies of land: decolonizing narratives, storying & literature / Sandra Styres -- Haa Shageinyaa : 'point your canoe downstream and keep your head up!' / Naadli Todd Lee Ormiston -- Rez ponies and confronting sacred junctures in decolonizing and indigenous education / Kelsey Dayle John -- River as lifeblood, river as border : the irreconcilable discrepancies of colonial occupation from/with/on/of the frontera / Marissa Muñoz -- Indigenous oceanic futures: challenging settler colonialisms & militarization / Noelani Goodyear-Ka'opua -- The Ixil university and the decolonization of knowledge / Giovanni Batz -- Decolonizing indigenous education in the postwar city : native women's activism from Southern California to the Motor City / Kyle T. Mays & Kevin Whalen -- Queering indigenous education / Alex Wilson with Marie Laing -- Colonial conventions : institutionalized research relationships and decolonizing research ethics / Madeline Whetung and Sarah Wakefield-- Decolonization for the masses? : grappling with indigenous content requirements in the changing Canadian post-secondary environment / Adam Gaudry & Danielle E. Lorenz -- E kore au e ngaro, he kakano I ruia mai i rangiatea (I will never be lost, I am a seed sown from Rangiatea) : te wananga o raukawa as an example of educating for indigenous futures / Kim McBreen -- Designing futures of identity : navigating agenda collisions in Pacific disability / Catherine Picton and Rasela Tufue-Dolgoy -- Decolonizing education through transdisciplinary approaches to climate change education / Teresa Newberry and Octaviana V. Trujillo -- With roots in the water : revitalizing straits salish reef net fishing as education for well-being and sustainability / Nicholas Xemtoltw Claxton & Carmen Rodríguez de France -- Walya'asuk'i naananiqsakqin : at the home of our ancestors: ancestral continuity in indigenous land-based languag immersion / Chuutsqa Layla Rorick.
Includes bibliographical references and index.
Keywords: Indigenous peoples -- Education -- Case studies